The Influence of The Teacher Working Group Program (KKG) on Teacher Professionals in State Madrasah Ibtidaiyah in Banda Aceh City - Nurmalisa, Reni; Ismail, Ismail; Khairuddin, Khairuddin (JETL (Journal of Education, Teaching and Learning), 2024)
The aim of this research is to find out whether the KKG Program is effective in increasing the professionalism of Banda Aceh City State Madrasah Ibtidaiyah Teachers. This research uses experimental research with a qualitative and quantitative approach. The sample for this research was 6 MIN teachers in Banda Aceh City who were selected using a saturated sampling technique. Data collection techniques use observation, interviews, and teacher ability test results. The data analysis technique used is integrated quantitative and qualitative. To describe the KKG program that has been implemented, qualitative analysis was used. Meanwhile, to determine the effectiveness of the KKG on professional teachers, a paired sample t test was used with the SPSS version 25.0 program. Based on research findings, it was found that there were significant differences in the teaching profession before and after the implementation of the KKG program at MIN Banda Aceh City. The results of the hypothesis test show 0.002 < 0.005, which means there is a significant influence of the KKG program on the teaching profession. The pretest data shows an average value of 58.78 and the posttest shows an average value of 80.56 indicating a 22% improvement. The conclusion of this research shows that the KKG program has an influence on improving the professionalism of State Madrasah Ibtidaiyah teachers in Banda Aceh City.